ANDROID-BASED APPLICATION OF SPEECH TO TEXT AS A STRATEGY TO IMPROVE STUDENTS' WRITING COMPETENCE: A CASE STUDY IN PUSTAKA RUMAH ALOY WRITING TRAINING COMMUNITY IN PONTIANAK, INDONESIA - Chairil Effendy; Dedy Ari Asfar; Syarifah Lubna; Binar Kurniasari Febrianti; Riani Riani (STKIP Singkawang, 2022)
This paper describes strategy learning for stories writing learning by applying an android-based application of speech to text. This application media has not been used optimally in text-based learning in Indonesia. Data analysis applied a qualitative approach without using statistical calculations. Data analysis was conducted through three stages that are: reducing data, presenting data, and drawing conclusions. As a result, the writing strategy applying the android based application of speech to text was proven and able to improve the story writing skills of junior high school students in the writing training community named Pustaka Rumah Aloy in Pontianak, Indonesia. The application of the speech to text showed better results on the students' ability to write stories and the writing class became more fun and enjoyable.